Kenya after 50 : reconfiguring education, gender, and policy - Koster, Mickie Mwanzia; Kithinji, Michael Mwenda; Rotich, Jerono P. (African histories and modernities., 2016)
This book explores the key milestones in education, gender, and policy that Kenya has achieved since independence, the challenges of this experience, and the future prospects. This edited collection of chapters also aims to illuminate the lessons learned from the experiences of the postcolonial period as well as postulate on the way forward. Through this exploration of the Kenyan experience since independence, the authors present an optimistic view that despite the many obstacles and challenges, the country still has promising prospects as a nation.